Analysis of Quercetin from Allium cepa L. Skin Waste in Inhibiting α-Amylase: An Alternate Therapeutic Drug to Treat Diabetes - Muthahhari, Muhammad Zaky; Qordhowi, Muhammad Hisyam; Bonardi, Mohammad Rafi; Sofiani, Tania; Simanjuntak, Samuel Balapradana; Mustari, Eri (School of Life Sciences and Technology, Institut Teknologi Bandung, 2025)
Type 2 diabetes is a chronic metabolic disease characterized by an increase in blood sugar due to insulin resistance as well as the decline of insulin production by the pancreas. Quercetin is a flavonoid secondary metabolite that could be utilized as an α-amylase inhibitor and can potentially be used as a therapeutic drug in type 2 diabetes treatment by inhibiting starch hydrolysis in the human body. This research aims to determine the quercetin yield of Allium cepa L. skin waste, evaluate the α-amylase inhibitory properties of the extracted quercetin, and delve into the molecular mechanism of α-amylase inhibition by quercetin. Methods that were used in this research consisted of sample collection and preparation, quercetin extraction, testing for quercetin content in extract by spectrophotometry and HPLC, as well as testing for α-amylase inhibition by quercetin. Quercetin extraction produced 1.52 g of dry extract, yielding 16.8 mg of extract per g of dry shallot skin. Spectrophotometric analysis yielded 3.37 mg of quercetin per gram of dried shallot skin, while HPLC yielded 3.99 mg/g. The shallot skin extract inhibited α-amylase with an IC50 of 348.2 µg/mL. In comparison, acarbose had a more potent inhibitory effect, with an IC50 of 237.4 µg/mL. Quercetin inhibits α-amylase by forming hydrogen bonds with the active sites of the enzyme (Asp197, Glu233, and Asp300).